Early expansive single sided laminoplasty decompression treatment severe traumatic cervical spinal cord injury - Yang, Chaohua; Wang, Qing; Xu, Shuang; Guan, Can; Li, Guangzhou; Wang, Gaoju (Frontiers in Surgery, 2022)
Background: Severe traumatic cervical spinal cord injury (tcSCI) is a disastrous event for patients and families. Maximizing spinal cord function recovery has become the primary therapeutic goal. This study investigated the effect of early extensive posterior decompression on spinal cord function improvement after severe tcSCI. Methods: A retrospective review of 83 consecutive patients who underwent extensive open-door laminoplasty decompression within 24 h after severe tcSCI (American Spinal Injury Association (ASIA) impairment scale (AIS) grade A to C) between 2009 and 2017 at our institution was performed. The patient clinical and demographic data were collected. Neurological functional recovery was evaluated according to the Japanese Orthopaedic Association (JOA) score system, ASIA motor score (AMS) and AIS grade. Results: Among the 83 patients initially included, the baseline AIS grade was A in 12, B in 28, and C in 43. Twenty-three patients (27.7%) had a high cervical injury. Cervical spinal stenosis (CSS) was identified in 37 patients (44.6%). The mean intramedullary lesion length was 59.6±20.4 mm preoperatively and 34.2±13.3 mm postoperatively (p<0.0001). At the final follow-up visit, an improvement of at least one and two AIS grades was found in 75 (90.4%) and 41 (49.4%) patients, respectively. 24 (64.9%) patients with an improvement of least two AIS grades had CSS. The mean AMS and JOA score were significantly improved at discharge and the final follow-up visit compared with on admission (p<0.0001). Conclusions: Our results suggest that early expansive laminoplasty decompression may improve neurological outcomes after severe tcSCI, especially in patients with CSS. Larger and prospective controlled studies are needed to validate these findings.